ATMOSFER SEKOLAH DASAR DAN IMPLIKASINYA BAGI PENDIDIKAN GURU SEKOLAH DASAR - Maryono Maryono (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Primary School Teacher Education (PGSD) is a study program that has a mandate to produce a primary school teacher. Therefore, PGSD implementing classes to provide students master the competencies of primary school teachers. Recognizing that the primary school at the center of the assessment in lectures in primary school teaching, deserves to be discussed many things about education in primary school. After that, the educational implications need to be addressed in the elementary school for lectures in primary school teaching.According to dynamization of education in primary schools, there are a number of dominant value and feasible in primary school teaching. The values in question are (1) the primary school as a center of education, meaning education in primary schools do not just happen in the classroom, also outside the classroom, and (2) the primary school as a cultural center, with activities (1) the development of logic, (2) the development of ethics, (3) development of aesthetics, and (4) development practices. PGSD development as a center of education as implemented in primary schools so that graduates PGSD feasible accustomed to education that is not only happening in the classroom also conducted education outside the classroom. Graduates PGSD in carrying out his duties as a primary school teacher to implement the education both inside and outside the classroom had no difficulty because it has been socialized in PGSD with such education. Likewise PGSD development as a cultural center.Keywords: primary school, elementary school teacher education